Association Between Intradialysis Hypotension and Interdialytic Weight Gain in Deceased Hemodialysis Patients at Banyumas Regional General Hospital - Gigih Rahmandanu Poernomo; Dwi Lestari Partiningrum; Lestariningsih Lestariningsih; Ayudyah Nurani; Arwedi Arwanto; Shofa Chasani; Haidar Alatas (Indonesian Journal of Kidney and Hypertension, 2025)
Background: Intradialytic hypotension (IDH) occurs in 5-40 percent of chronic kidney disease (CKD) with hemodialysis patients, it is associated with increased cardiovascular events and mortality. High Interdialytic Weight Gain (IDWG) requires higher ultrafiltration, increases the incidence of IDH, associated with a worse prognosis, patients with a history of diabetes are at higher risk. Objective: This study aimed to assess the association between IDWG and the occurrence of IDH in deceased patients undergoing hemodialysis, with a particular focus on the differences between diabetic and non-diabetic patients Methods: A retrospective study was conducted for one year at Banyumas Regional General Hospital, involving deceased hemodialysis patients. IDWG was calculated as the average of the last three hemodialysis sessions. Patients were further categorized based on their history of diabetes. Results: Among 37 deceased hemodialysis patients, 56.8% experienced IDH, including 50% of those with diabetes mellitus. IDWG was normally distributed (p = 0.283) and showed a weak but statistically significant correlation with IDH (r = 0.333, p = 0.044). Logistic regression indicated that each 1% increase in IDWG was associated with an 8% increase in the predicted probability of IDH. Diabetic status did not significantly modify this association (p = 0.772). Conclusion: Higher IDWG was associated with increased incidence of IDH in deceased hemodialysis patients, independent of diabetic status.